Management of Traumatic Spinal Fracture in the Coronavirus Disease 2019 Situation - Sornsa-ard, Tuanrit (Asian Spine J, 2020)
The coronavirus outbreak was labeled a pandemic by the World Health Organization in 2020. Patients who require spine surgery should receive coronavirus disease 2019 (COVID-19) screening to prevent nosocomial cross-infection before surgery. However, spine fracture and spinal injury are critical and serious, and there are no standard protocols for management. This article aims to propose a treatment algorithm for the management of traumatic spine fracture during the COVID-19 pandemic.